Development and psychometric testing of the Attitudes, Subjective Norms, Perceived Behavioural Control, and Intention to Pursue a Career in Mental Health Nursing scale - Wilbourn, Mark; Salamonson, Yenna; Ramjan, Lucie; Chang, Sungwon (International journal of mental health nursing, 2018)
The aim of the present study was to develop and test the psychometric properties of the Attitudes, Subjective Norms, Perceived Behavioural Control, and Intention to Pursue a Career in Mental Health Nursing (ASPIRE) scale, an instrument to assess nursing students' intention to work in mental health nursing. Understanding the factors influencing undergraduate nursing students' career intentions might lead to improved recruitment strategies. However, there are no standardized tools to measure and assess students' intention to pursue a career in mental health nursing. The present study used a cross‐sectional survey design undertaken at a large tertiary institution in Western Sydney (Australia) between May and August 2013. It comprised three distinct and sequential phases: (i) items were generated representing the four dimensions of the theory of planned behaviour; (ii) face and content validity were tested by a representative reference group and panel of experts; and (iii) survey data from 1109 first‐ and second‐year and 619 third‐year students were used in exploratory and confirmatory factor analyses to test the factorial validity of the scale. Internal consistency was measured using Cronbach's alpha. Items generated for the ASPIRE scale were subject to face and content validity testing. Results showed good factorial validity and reliability for the final 14‐item scale. Principal axis factoring revealed a one‐factor solution, the hypothesized model being supported by confirmatory factor analysis. The ASPIRE scale is a valid and reliable instrument for measuring intention to pursue a career in mental health nursing among Bachelor of Nursing students.